Association of SNP markers in different candidate genes with growth performance of Landrace × Ghurrah crossbred pigs - NAHA, B C; GAUR, G K; SAINI, B L; SAHOO, N R; PANDA, S (The Indian Journal of Animal Sciences, 2022)
The objective of this study was to assess the polymorphic dispersion of SNP markers in candidate growth genes and their impact on growth performance of Landlly (Landrace × Ghurrah crossbred) pigs. PCR-RFLP procedure was utilized to differentiate the genotypes at marker loci. Most of the SNP loci [MC4R (AA, AG and GG); PGK2 (GG, GT and TT); CTSD (AA, AG and GG); CTSK (AA, AG and GG); SLC27A4 (AA, AG and GG); MYC (CC, CT and TT); and LEP (CC, CT and TT)] had 3 genotypes with varying frequency. Only 2 genotypes [AA (59%) and AG (41%)] were noticed for GHRL. IGF-1 and CTSZ SNPs were monomorphic for AA genotype. Allelic frequencies for these SNPs (MC4R, PGK2, CTSD, CTSK, CTSZ, SLC27A4, GHRL, MYC, IGF-1and LEP) were 0.51 and 0.49 (A/G), 0.66 and 0.34 (G/T), 0.55 and 0.45 (A/G), 0.48 and 0.52 (A/G), 1.00 (A), 0.69 and 0.31(A/G), 0.80 and 0.20 (A/G), 0.22 and 0.78 (C/T), 1.00 (A) and 0.47 and 0.53 (C/T), respectively. Impact of PGK2, CTSK, GHRL and LEP SNP was meaningful on the body weight at birth. MC4R had significant impact on body weight at 6 weeks. SLC27A4 and LEP SNP significantly affected body weight at 32 weeks. This investigation suggested MC4R, PGK2, CTSK, SLC27A4, GHRL and LEP SNPs as potential markers for improving growth performance in Landlly pigs.